Determination of fatty acid composition of winter consumer and UHT milk samples in Slovenia - Vekoslava STIBILJ; Mojca KOMAN RAJŠP (Acta Agriculturae Slovenica)
The aim of our work was to determine fatty acid composition of winter consumer - pasteurised and UHT - ultra high temperature heated milk samples from five different Slovene geographical regions (five different Slovene dairies). All milk samples (homogenised, pasteurised or sterilised, 3.2 % milk fat) were collected locally from February to March 1997. Lipid extraction preceeding fatty acid methyl esters (FAME-s) preparation for gas chromatography is time consuming and cumbersome. We omitted the lipid extraction and performed in situ transesterification (ISTE) by heating lipid - containing milk at 90o C for 10 min after adding 0.5 N NaOH in methanol for methanolysis and continued heating another 10 min for further methylation after adding 12 % BF3 in methanol. For milk, FAME-s prepared by ISTE showed fatty acid compositon virtually identical to FAME-s prepared after lipid extraction. Due to simplicity, speed and reduced organic solvent usage, we used ISTE method for determination milk fatty acid composition. To the best of our knowledge, we did not find any literature data about fatty acid composition of Slovene cow milk so we compared our results with literature data of milk fatty acid composition from other countries and found good accordance.